Histology of microscopic colitis—review with a practical approach for pathologists. Issue 5 (12th January 2015) - Langner, Cord; Aust, Daniela; Ensari, Arzu; Villanacci, Vincenzo; Becheanu, Gabriel; Miehlke, Stephan; Geboes, Karel; Münch, Andreas; the Working Group of Digestive Diseases of the European Society of Pathology (ESP); the European Microscopic Colitis Group (EMCG)
<x xml:space="preserve">Abstract</x> Microscopic colitis has emerged as a major cause of chronic watery non‐bloody diarrhoea, particularly in elderly females. The term is used as an umbrella term to categorize a subgroup of colitides with distinct clinicopathological phenotypes and no significant endoscopic abnormalities. Lymphocytic colitis is defined by an increased number of surface intraepithelial lymphocytes, and collagenous colitis by a thickened collagen band underneath the surface epithelium. There is increased inflammation in the lamina propria, but only little or no crypt architectural distortion. Incomplete and variant forms showing less characteristic features have been reported under different names. The differential diagnosis mainly includes resolving infectious colitis and changes related to the intake of drugs such as non‐steroidal anti‐inflammatory drugs. Substantial clinical and histological overlap between lymphocytic and collagenous colitis has been described, raising the suspicion that the conditions are two histological manifestations of the same entity, possibly representing different manifestations during the disease course or different stages of disease development. In this review, we provide a practical approach for pathologists, with a focus on diagnostic criteria and differential diagnosis, and discuss recent insights into the pathogenesis of disease and the relationship with classic chronic inflammatory bowel disease, i.e. Crohn's disease and ulcerative colitis.